The Effectiveness of the Marriage Management Information System (SIMKAH) Program in Administration Services of the Religious Affairs Office (KUA) District Marisa, Pohuwato Regency - Djamila Podungge; Saiful Annam; Sri Yulianty Mozin (Governance: Jurnal Ilmu Administrasi Publik, 2023)
The purpose of this study was to determine and analyze (1) the effectiveness of the Marriage Management Information System (SIMKAH) program in the administrative services of the Office of Religious Affairs (KUA) Marisa District, Pohuwato Regency, and (2) the factors that determine the effectiveness of the Marriage Management Information System (SIMKAH) program. ) in the administrative service of the Office of Religious Affairs (KUA) Marisa District, Pohuwato Regency. This study uses a qualitative approach. The technique used to obtain the data is the technique of observation, interviews and documentation. Data analysis techniques are carried out through data collection, data reduction, data presentation and conclusion drawing/verification. The process of checking the validity of the data is carried out through diligent observation and triangulation. The results of this study are (1) the SIMKAH program at the KUA administration service, Marisa District, Pohuwato Regency has not been effective; (2) the factors that become obstacles in realizing the effectiveness of the SIMKAH program are (a) the number of human resources that have not met the needs and lack of technical training for operators, (2) inadequate service support facilities both quantitatively and qualitatively, (3) system maintenance information has not been carried out regularly, and (4) the factor of public awareness of the use of SIMKAH is still low.